Pancreatic pseudocyst in children: a rare medical entity - Pareek, Prashant; Agrawal, Neelabh (International Surgery Journal, 2016)
Pancreatic pseudocyst (PCC) is an extremely rare medical condition in pediatric population. The history of acute pancreatitis holds significance as it may progress into formation of such pseudo cyst in children. Acute pancreatitis may result from abdominal injury, biliary tract disease, viral illness, states of intracranial hypertension and steroids. However blunt abdominal trauma is the most common cause of pancreatic pseudocysts in children. Here we report a case of blunt abdominal trauma in a six-year-old child that resulted in pancreatic pseudocyst which was treated effectively with cystogastrostomy.